The optoelectronic properties of boron nitride nanotubes of armchair (7, 7) and zigzag (12, 0) types: A theoretical study - El Ouardi Oumaima; Boutahir Mourad; Fakrach Brahim; Chadli Hassan (E3S Web of Conferences)
In this article, the electronic and optical properties of single-walled boron nitride nanotubes (SWBNNTs) in zigzag (12, 0) and armchair (7, 7) configurations were examined using density functional theory (DFT) with the Vienna Ab initio Simulation Package (VASP). The analysis shows that SWBNNTs exhibit electronic characteristics with a density of states and an electronic band gap around 4 eV. Regarding optical properties, the calculations reveal key features such as absorption, reflection, and dielectric constant, with a notably strong absorption peak in the ultraviolet region. These results highlight the potential of SWBNNTs for applications in optoelectronic devices.